Análise da genotoxicidade e da frequência de toxoplasmose em indivíduos diagnosticados com esquizofrenia - Pedroso, Thays Millena Alves (2018)
Schizophrenia is a complex mental disorder in which the individual has difficulty distinguishing between what is real and what is imaginary. It is a multifactorial disease in which factors such as environment, genetic predisposition, toxoplasmosis and biochemical changes in the brain are closely related to the severity of the disease, both positive and negative symptoms. The present study aimed to evaluate the prevalence of toxoplasmosis and genotoxicity of Toxoplasma gondii in individuals diagnosed with schizophrenia. The ELISA immunoenzymatic assay was used to evaluate the seropositivity to T. gondii and the comet assay to detect genotoxic damage. In the group, 69 individuals and 45 individuals who did not have schizophrenia or any mental disorder were analyzed. A statistically significant difference (p <0.05) was observed when the mean age and tobacco use frequency were analyzed, the individuals diagnosed with schizophrenia showed higher seropositivity (p <0.01) when compared to the control group. Analyzing the mean ± SD (standard deviation), they showed greater genotoxic damage in the case group in relation to the control group. In addition, it was observed that the association between the genotoxic damage of the case group with sex, IgG, disease, smoking and alcoholic beverages presented values of p> 0.05. Thus, it can be concluded that there was no significant difference when comparing the genders to the prevalence of toxoplasmosis in the individuals diagnosed with schizophrenia. In the case group it was possible to verify greater genotoxic damage in the DNA than in the control group.